INVESTMENT CLIMATE OF UKRAINE AND DIRECTIONS OF ITS IMPROVEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article noted that investment activity is the basis of the economic development of every country and allows to accelerate the implementation of innovations, update the real sector of the country's economy, and increase competitiveness. The authors analyzed the approaches of scientists to the identification of the concept of "investment climate", and systematized them. Positive and negative factors influencing its formation are identified, among which the following are noted: legislative and regulatory framework, tax system, political stability, economic development, level of corruption, etc.An analysis of the dynamics of direct investment inflows to Ukraine over the past six years was carried out, and the reasons for their reduction and increase in each of the periods were determined. It is substantiated that the main reasons for the decrease in the volume of foreign investments in Ukraine during 2018-2021 are: a high level of corruption in the country, distrust of the judicial system, instability of the national currency, economic and political situation, monopolization of markets and an unfavorable investment climate. The main types of economic activity, in which investments are most directed, are considered. The largest investor countries in the economy of Ukraine for 2021 have been identified, namely: Cyprus, the Netherlands, Switzerland, Poland and others. The dynamics of the Investment Attractiveness Index during 2018 - 2022 were analyzed. The factors influencing the formation of Ukraine's investment climate in modern economic conditions, taking into account the status obtained by Ukraine as a member of the EU, were determined. A number of measures are proposed to improve the investment climate of Ukraine during the post-war recovery period.
Keywords: investments, investment climate, investors, direct investments, investment attractiveness.